From Distraction to Dialogue: A Narrative Analysis of Classroom Management as an Act of Co-Constructing Mutual Respect - Laila Ngindana Zulfa; Sota Yamamoto; Aung Myint (International Journal of Educational Narratives, 2026)
Background. Classroom disruptions are often addressed through punitive or authoritarian strategies that suppress student agency rather than foster meaningful engagement. The prevailing discourse frames classroom management as a mechanism of control, largely neglecting its relational and dialogic dimensions. This study departs from that reductive view by examining how teachers and students collectively negotiate behavioral norms through sustained communicative interaction. Purpose. This study aims to explore how classroom management practices function as a co-constructive process through which mutual respect is dialogically produced between teachers and students. Method. A narrative inquiry design was employed, drawing on in-depth interviews, classroom observations, and reflective journals from six secondary school teachers across diverse institutional contexts. Data were analyzed through thematic narrative analysis, attending to relational episodes, turning points, and discursive patterns. Results. Findings reveal that effective classroom management transcends behavioral correction; it emerges as an ongoing, intersubjective dialogue in which teachers reframe disruptions as opportunities for relational repair and mutual recognition. Three narrative patterns were identified: repositioning authority through empathetic listening, transforming conflict into collaborative problem-solving, and sustaining respect through consistent communicative reciprocity. Conclusion. Classroom management, when approached dialogically, serves as a pedagogical act of co-constructing mutual respect rather than enforcing compliance. These findings call for a paradigmatic shift in teacher education toward relational and dialogic competencies.